The Effect Of Work Experience On Worker Performance: Workload And Self-Efficacy As Moderating Roles - Irsyad Robbani; Wahyu Maulana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
A thorough examination of the research findings revealed that work experience has a positive and considerable impact on worker performance. In addition, workload can reduce the level of influence of work experience on worker performance whereas the association between work experience and worker performance can be strengthened by self-efficacy. The results obtained from this study directly answer the main objectives of the study, namely to explore the extent to which work experience affects worker performance, as well as to evaluate how workload and self-efficacy moderate this influence, making it stronger or weaker. This study focused on the entire furniture industries spread across Karduluk Village and was designated as the object of analysis to obtain a comprehensive empirical picture. The research sample consisted of 279 respondents from a total population of 920 individuals working within the village and was determined using the Slovin formula, with the sampling technique, namely stratified random sampling. The research approach was quantitative, utilizing the SmartPLS 4.0 application as the main tool for testing using the SEM-PLS method. The head of each hamlet sent the research participants a digital questionnaire with fifteen statements as part of the data collection process.